The Utilization of VO₂Max Data as Archery Athlete Selection and Monitoring Instrument - I Gede Ari Septena Putra; Kadek Yogi Parta Lesmana; I Made Satyawan (Universitas Negeri Semarang, 2026)
In sports management in schools, objectivity in the athlete selection process is often compromised due to the lack of use of measurable and scientific-based physical data. In archery, aerobic capacity, especially VO₂max, plays an important role in maintaining physical stability, concentration, and heart rate stability during matches. This study aims to implement VO₂max audit as a strategic instrument in the selection, evaluation, and monitoring of archery athletes at SMK Negeri Bali Mandara. A descriptive quantitative approach was used with 21 archery athletes. VO₂max was measured using the Multistage Fitness Test (MFT). The results showed that athletes' aerobic capacity ranged from 22.93 to 38.84 ml/kg/min, with the majority (52.4%) in the